2009
DOI: 10.1057/ejdr.2009.23
|View full text |Cite
|
Sign up to set email alerts
|

Part of the Disease Or Part of the Cure? Chinese Investments in the Zambian Mining and Construction Sectors

Abstract: China's role in African development is much debated among academics as well as among private sector organisations, trade unions and politicians. Notwithstanding the recent upsurge of interest, the lion's share of the current studies on 'China in Africa' is still based on a combination of aggregate figures and sporadic information from news agencies. Although much of the hysteria surrounding the 'China in Africa' debate has now evaporated -at least from the scholarly debate -the local debate is highly politicis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Given the conditions of entry for Chinese firms, they have been largely limited to acquiring existing mines and hard-to-reach deposits. Recent purchases include the Chambishi mine in Zambia, which now includes a special economic zone (SEZ) and functions as a hub for Chinese investment in the country (Kragelund, 2009), the Husab project in Namibia, which contains one of the world’s largest uranium deposits, the Kamoa Copper deposit in the Democratic Republic of the Congo (DRC), and a series of smaller mines throughout South Africa, including the Bakubung platinum mine and SAIL mining group’s Black Chrome mine (Interview, Mining Executive, October 2017, Johannesburg). Additionally, Chinese SOEs have invested large amounts of capital into foundries and processing plants throughout the continent, including a recent $700 million investment in an iron ore processing plant in Sierra Leone (Corcoran, 2017).…”
Section: Chinese Megaprojects In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Given the conditions of entry for Chinese firms, they have been largely limited to acquiring existing mines and hard-to-reach deposits. Recent purchases include the Chambishi mine in Zambia, which now includes a special economic zone (SEZ) and functions as a hub for Chinese investment in the country (Kragelund, 2009), the Husab project in Namibia, which contains one of the world’s largest uranium deposits, the Kamoa Copper deposit in the Democratic Republic of the Congo (DRC), and a series of smaller mines throughout South Africa, including the Bakubung platinum mine and SAIL mining group’s Black Chrome mine (Interview, Mining Executive, October 2017, Johannesburg). Additionally, Chinese SOEs have invested large amounts of capital into foundries and processing plants throughout the continent, including a recent $700 million investment in an iron ore processing plant in Sierra Leone (Corcoran, 2017).…”
Section: Chinese Megaprojects In Africamentioning
confidence: 99%
“…Structural transformation, as expressed through the sophistication of exports or the creation of high labour productivity sectors simply has not happened on a large scale throughout SSA. Research into the topic, (Fessehai and Morris, 2013; Kragelund, 2009; Lee, 2014, 2017) has shown that due to cost factors and difficulties in input procurement in parts of SSA, Chinese mining firms typically import most inputs from abroad. This procurement strategy can marginalize the role of local suppliers in the mining value chain, minimize opportunities for technology transfer and create vertically integrated enclave developments.…”
Section: Chinese Megaprojects In Africamentioning
confidence: 99%
“…Tender documents usually stipulate the grade categories of companies that can bid. There are no Zambian-owned companies at grades 1 and 2 (Kragelund, 2009). quality assurance capabilities among Zambian suppliers and information asymmetry that limits mining corporations' knowledge of what is available locally, resulting in very low degrees of local content (Fessehaie & Rustomjee, 2018).…”
Section: [Figure 2 Near Here]mentioning
confidence: 99%
“…Another strand focuses on the argument that migration of Chinese workers into Africa is part of the competitive game, although it has raised concerns (Mohan and Tan‐Mullins , 588). Focusing on investments, others highlight that Chinese investments in two Zambian sectors are not different from mainstream foreign investment (Kragelund , 644) and Chinese investments in Zambia are also broadly consistent with the rule of free market competition (Kamwanga and Koyi , 6). While Chinese investments in Africa are resource and “weak institutions” driven, this is not different from the motivations behind Western FDI (Kolstad and Wiig , 31) or China's move into Africa is not different from that of the West centuries ago which was motivated primarily by the need for raw materials for her industries and markets for her finished products (Osei and Mubiru , 1).…”
Section: Schools Of Thought and Argumentsmentioning
confidence: 99%